SIMBOL-SIMBOL DALAM PERIBADATAN HARI PENTAKOSTA DI GEREJA MERTA URIP LUKLUK, BADUNG - Narawati, Made (Prosiding Seminar Nasional Bahasa Ibu, 2025)
Protestant Christian Churches in Bali (GKPB) are scattered all over Bali where the majority of the people are Balinese. One of the churches is GKPB Merta Urip Lukluk in Badung Regency. The pattern of worship every Sunday and other religious days is used Balinese as the language of instruction interspersed with Indonesian. The implementation of Pentecost worship in the Church which is held every May every year uses various means as symbols of worship events such as clothing and language used, pictures of tongues of fire, pictures of wind, doves, candles and the color red. In semiotic studies, these symbols have profound meanings and functions for the lives of the people, namely enriching the spiritual experience of the people and strengthening the relationship between Christian faith and Balinese culture.